Edukasi Melalui Konten Media Sosial Terhadap Sikap dan Pemahaman Ibu tentang ASI Eksklusif - Nurun Nandifah; Fania Khoirunnisa; Dwi Astuti; Dyah Ayu Utari (Politeknik Kesehatan Kementrian Kesehatan Semarang, 2025)
Breast milk is the first source of food for babies that is obtained directly from the mother. The mother's understanding and demeanor play a really imperative part within the success of exclusive breastfeeding, so the foremost endeavors made within the community are to supply early instruction to moms and families so they can get it the significance of exclusive breastfeeding. To extend mothers' information around it, curiously and enlightening instructive media is required. Breastfeeding education can be done using various media, one of which is video media which is distributed on social media. This research aims to analyze the influence of breastfeeding education through social media content on mothers' attitudes and understanding regarding exclusive breastfeeding. This exploration for exploratory decisions through pre-test and post-test. The population was mothers who had children aged 0-3 months at the Children's Polyclinic at PKU Muhammadiyah Mayong Hospital, totaling 40 patients. The sample used in this research was 36 respondents. If the data is not normal, then use the Wilcoxon test and if it is normally distributed then use the paired t test. The research results explained that there was an influence of breastfeeding education through social media content on attitudes regarding exclusive breastfeeding (0.000) and understanding of breastfeeding (0.000).